Facile microwave synthesis of Zinc Ferrite@NCDs for photocatalytic degradation of fluoroquinolone antibiotics - Kaushal, Neha; Sarraf, Sonu; Basu, Aviru Kumar; Mishra, Sunita; Saha, Avishek (Materials Chemistry and Physics, 2024)
Zinc ferrite (ZnFe2O4) composites have attracted growing interest in photocatalytic water purification. Herein, the hybrids of zinc ferrite and nitrogen-doped carbon dots (ZnF@x%NCDs) were synthesized via facile micro-wave synthesis. X-ray diffraction and Raman characterization confirm the formation of the spinel structure, and elemental composition has been analyzed by X-ray photoelectron spectroscopy. The photocatalytic activity of ZnF@x%NCDs was evaluated via the decomposition of ciprofloxacin and norfloxacin under visible light illumination. We noted that 20 % weight loading of NCDs led to the highest (similar to 79.2 %) ciprofloxacin (CIP) degradation. Diffuse reflectance measurements demonstrate the reduction of the band gap in composites ZnF@20%NCDs (1.91 eV) compared with bare ZnF (2.03 eV); moreover, the hybridization of zinc ferrites with NCDs results in enhanced photocurrent density and surface area. The effect of experimental parameters, including the role of photocatalyst dosage, pH value, and initial concentration of pollutants on the degradation of CIP, have also been investigated.
Keywords: Carbon dots; Ciprofloxacin degradation; Norfloxacin degradation; Photocatalysis; Zinc Ferrite